Security, Welfare and Economic Considerations in the Embrace of Investments from Emerging Economies: The Case of Portugal - Pal, Timea (Policy Response to Emerging Economy FDI in Portugal, 2016)
Increasing flows of foreign direct investments (FDI) from emerging economies over the last decade have often resulted in resistance among advanced economies. This article examines responses in Portugal, an important destination of international investments from Angola, Brazil and China. Contrary to other advanced economies, Portugal retained a highly receptive policy framework, even as it experienced some resistance at the political and public levels. The analysis makes three essential contributions. First, it distinguishes between FDI resistance at policy, political and public levels that have been largely conflated so far. Second, it underlines the importance of economic considerations that can counterbalance concerns over national security and societal welfare, two common mechanisms associated with resistance in other countries. Third, it illustrates with the case of FDI from Angola, that under some conditions, concerns over welfare in the country of origin, rather than in the country of destination, can fuel calls to restrict investments.